KINERJA KEUANGAN BANK KONVENSIONAL DAN DIGITAL SEBELUM DAN SELAMA PANDEMI COVID-19 - Monika Estefani Susanto; Arthik Davianti (Program Studi Diploma III Akuntansi Fakultas Ekonomi dan Bisnis Universitas Mataram, 2023)
This study aims to determine the financial performance of conventional banks, digital banks, and conventional banks with digital services before and during the COVID-19 pandemic. This research is descriptive quantitative research with the data source used as secondary data. The data analysis technique uses financial ratio analysis. These CAMELS factors are classified as the capital ratio, asset quality ratio, management ratio, earnings ratio, liquidity ratio, and sensitivity to market risk ratio. The results show that conventional banks with digital services have the best financial performance compared to the other two types of banks. It can be seen that BCA has the best management, profitability and liquidity performance, while BTPN has the best asset quality and sensitivity to market risk performance. In contrast, as digital banks, Bank Jago and Bank Neo Commerce have the worst financial performance among other banks based on asset quality, management, and profitability performance.